The Diplomatic Role of the Non-Aligned Movement in Strengthening Contemporary International Relations - Younis Talat AL-Dabbagh (QALAAI ZANIST JOURNAL, 2024)
Our choice is due to the study of the diplomatic role of the Non-Aligned Movement in strengthening contemporary international relations, with the aim of revealing the effects and transformations in the contemporary international system that resulted from the repercussions of this movement, which raised in its content a lot of discussion and controversy, starting from definition, origin and development, And going through defining the dimensions of this movement, its manifestations, and the nature of the driving forces for it in international relations, and finally getting acquainted with its diplomatic and political role. In light of the five principles of the Bandung Conference in (1955 AD), which are: peaceful coexistence, mutual respect for the sovereignty and territorial integrity of member states, non-interference in internal affairs, and non-aggression between states, equality and mutual interests, the movement had a prominent role in resolving and settling conflicts between states and mitigating Therefore, it was dependent on the principles that aim at peaceful coexistence and avoiding wars and conflicts that arise between states by following a policy of positive neutrality and rejecting the policy of bases, alliances and military blocs. It actively sought, through effective diplomacy, to confront the challenges and crises facing the countries of the world through good management of differences and the adoption of the principle of dialogue in finding sustainable solutions. In light of the great challenges that this movement faced under the new world order, and in a global system full of tensions, turmoil and crises, and international interactions that may warn of the outbreak of confrontations and wars if they are not properly managed.Here, the philosophy of the Non-Aligned Movement is evident, and through the principles it relies on, to play an important global role and through its effective diplomacy, through which it is keen to devote international efforts to work to consolidate international peace and security. It constitutes a platform for active joint diplomatic action that enhances relations and collective security, and works to establish world peace and mitigate international conflicts. Therefore, the movement is called upon to respond to current and emerging challenges in the future.